Qodiyatuz Zawaji bi al-Kitabiyyati fi Mizani al-Fatawa Ibra Usuli al-Mukhtalifati - Anwar, Saeful (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2024)
The issue of marriage with the Kitabiyya is an issue in which the jurists differed in their fatwas across different ages. The reason for their disagreement was their differing view of the issue based on the two matters. First: Understand the evidences from Qur’an and sunnah on which the case is based. Second: Putting the understanding of these evidences in the light of social conditions. Among the hypotheses of this research are, firstly, some fiqh experts have a fatwa about the permissibility of marrying a Kitabiyah based on the original law stated in the Qur'anic text, but they also mention their tendency for marriage to a Kitabiyah not to be carried out by a Muslim. Second, some fiqh experts have a fatwa about the detestable (karahah) of marriage with the Kitabiyah because of the difference between the conditions of the Muslims and ahl kitab today and the situation of Muslims and Ahl al-Kitab at the time when marriage was permitted by the Qur'an. The third: Some of fiqh experts issue a fatwa while it is permissible and while it is forbidden according to the evidence that coincides with marriage with kitabiyah, and the jurists did not forbid marriage with the Book absolutely because there are verses in the Koran that clearly allow it. Fourth, The difference in opinion on the fatwa of the fiqh experts on this issue is due to their different point of view on the legal basis of the matter, and the way they put their understanding in their condition when issuing the fatwa. fifth, The negative impact of allowing marriage with the Kitabiyah is more than the positive impact of it.